Boron nitride nanosheet modified spinnable organic-inorganic hybrid polyborazine and preparation method thereof
By introducing modified boron nitride nanosheets into the polymer pioneer, the spinnable organic-inorganic hybrid polyborazane was synthesized, which solved the problem of low crystallinity of boron nitride ceramic materials, and achieved the preparation of boron nitride ceramic materials with high crystallinity and excellent performance.
Patent Information
- Application Number
- CN202411976338.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-31
AI Technical Summary
During the preparation process, the transition process of the amorphous morphology to the crystalline state of the existing boron nitride ceramic materials is difficult to control, resulting in low crystallinity, which in turn affects its thermodynamic, electrical and mechanical properties.
By introducing modified boron nitride nanosheets into the polymer pioneer, a spinnable organic-inorganic hybrid polyborazane modified by boron nitride nanosheets was synthesized by chemical doping, and the crystallinity of the ceramic material was improved by using its chemical bonding properties.
It achieves high crystallinity, excellent mechanical properties and high density of boron nitride ceramic materials, providing the possibility of preparation of boron nitride ceramic fibers and ceramic materials.
Smart Images

Figure CN119775569A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of organic synthesis, and specifically relates to a spinnable organic-inorganic hybrid polyborazine modified by boron nitride nanosheets and a preparation method thereof, and also relates to a spinnable organic-inorganic hybrid polyborazine modified by boron nitride nanosheets and a synthesis method thereof. Background Art
[0002] Trace amounts of inorganic nanofillers can usually significantly affect the microstructure and properties of polymer substrate materials, but there are still few studies on inorganic nanofillers doped with boron nitride precursors (polyborazane).
[0003] Boron nitride ceramic materials have excellent high temperature resistance, ablation resistance, chemical corrosion resistance and wave transmission properties, and have broad application prospects in the fields of aviation, aerospace, energy, catalysis, etc. The polymer precursor method (PDCs) is widely used in the preparation of boron nitride ceramic materials because of its advantages such as the designable precursor molecular structure, high purity of ceramic products, and the ability to achieve uniform product structure and components by controlling the uniform distribution of components in the precursor polymer. Among them, the design and synthesis of suitable precursors are key technologies for the preparation of boron nitride ceramic materials suitable for different application fields, and have attracted much attention in recent years.
[0004] At present, a lot of research has been carried out on the preparation of boron nitride ceramic materials by polymer precursor conversion method. Various forms of polyborazane precursors have been synthesized, and their ceramic transformation process has been regulated in various ways. However, the boron nitride ceramic materials prepared so far have problems such as the difficulty in controlling the transformation process from amorphous state to crystalline state during the preparation process, and the low crystallinity of boron nitride ceramic materials, which makes it difficult to control the microstructure of boron nitride ceramic materials, thereby affecting their thermodynamic, electrical and mechanical properties.
[0005] Therefore, it is urgent to design and synthesize a spinnable polyborazine precursor that can be used to prepare highly crystalline boron nitride materials, so as to provide the possibility for regulating the microstructure of boron nitride ceramic materials and preparing high-performance boron nitride ceramic fibers and ceramic materials. Summary of the invention
[0006] In view of the problems that the boron nitride ceramic materials prepared in the prior art all have the problems of difficult control of the transformation process from an amorphous state to a crystalline state during the preparation process and low crystallinity of the boron nitride ceramic materials, the present invention provides a spinnable organic-inorganic hybrid polyborazine modified by boron nitride nanosheets and a preparation method thereof, and also a spinnable organic-inorganic hybrid polyborazine modified by boron nitride nanosheets and a preparation method thereof, the preparation process is simple, and can be used for large-scale production; the prepared boron nitride ceramic material has high crystallinity, which provides the possibility for further regulating the microstructure of the boron nitride material and preparing high-performance boron nitride ceramic fibers and ceramic materials, and enriches the types of boron nitride precursors.
[0007] The present invention aims to solve the problem that the currently prepared boron nitride ceramic materials have low crystallinity. By taking advantage of the adjustable molecular structure of the precursor in the polymer precursor conversion method, starting from the design of the polymer precursor molecular structure, a spinnable organic-inorganic hybrid polyborazane modified with boron nitride nanosheets is synthesized for the first time through chemical doping. Technical principle of the present invention:
[0008] (1) Preparation of modified boron nitride nanosheets:
[0009]
[0010] (2) Preparation of organic-inorganic hybrid polyborazine:
[0011]
[0012] The purpose of the present invention is achieved through the following technical solutions:
[0013] A method for preparing a spinnable organic-inorganic hybrid polyborazane modified by boron nitride nanosheets comprises the following steps:
[0014] (1) Preparation of modified boron nitride nanosheets:
[0015] Boron nitride nanosheets (BNNS) and a modifier were mixed at a mass ratio of 6:1, and then ball-milled in a high-energy ball mill. The resulting powder was then washed, filtered, dried, and dispersed in a solvent at a mass volume ratio of 2 g:10 mL to obtain a modified BNNS dispersion.
[0016] The modified BNNS dispersion, wherein the BNNS size is 100nm-10μm and the thickness is 10nm-20nm;
[0017] The modifier is an amino group-containing compound, selected from one or a mixture of NH2R1, NHR1R2 (R1, R2 = CH3, CH2CH3, CH2CH2CH3 or other alkyl) amine compounds and other amino group-containing compounds, in any proportion when mixed;
[0018] The solvent is selected from toluene, xylene and chlorobenzene;
[0019] (2) Preparation of organic-inorganic hybrid polyborazine:
[0020] At room temperature, the modified BNNS dispersion obtained in the previous step is added to the borazane oligomer solution at a mass ratio of 0.1%-0.5%, and the concentration of the borazane oligomer solution is 10mg / mL-100mg / mL. The solution is kept warm at low temperature to allow the modified BNNS to be doped into the borazane oligomer through chemical bonds and methods; the temperature is slowly raised to a high temperature and kept warm, and after cooling to room temperature, an organic-inorganic hybrid polyborazine is obtained;
[0021] The borazane is selected from one or a mixture of borane, cycloborazine, trichlorocycloborazine, alkylaminoborane or ammonia borane, and the mixture is in any proportion;
[0022] The oligomer is selected from a dimer, a trimer, and a tetramer;
[0023] The heat preservation at low temperature is a temperature of 60°C-160°C and a time of 1h-5h;
[0024] The slow heating to high temperature insulation is heating to 180°C-300°C, and the insulation time is 1h-15h.
[0025] In the present invention:
[0026] The ball milling process in step (1) is performed for 12 h to 48 h at a rotation speed of 400 r / min to 1000 r / min.
[0027] The modified BNNS dispersion described in step (1), wherein the BNNS has a size of 400 nm-2 μm and a thickness of 10 nm-20 nm.
[0028] The borazane described in step (2) is an organic polymer having a main chain containing a BNB six-membered ring structure, and is selected from one or a mixture of borane, cycloborazine, trichlorocycloborazine, alkylaminoborane, and ammonia borane.
[0029] The present invention also relates to a spinnable organic-inorganic hybrid polyborazine modified by boron nitride nanosheets, which is obtained by using the preparation method of the spinnable organic-inorganic hybrid polyborazine modified by the above boron nitride nanosheets. In the spinnable organic-inorganic hybrid polyborazine modified by boron nitride nanosheets, the modified boron nitride nanosheets and the polyborazane are combined by chemical bonding. The spinnable organic-inorganic hybrid polyborazane modified by boron nitride nanosheets has the following technical indicators:
[0030] (1) Boron nitride nanosheets and polyborazane are chemically bonded;
[0031] (2) high ceramic yield, specifically, ceramic yield ≥ 65%;
[0032] (3) Excellent spinnability, E η=1.0 kJ / mol.
[0033] The present invention also relates to a BN ceramic material, which is prepared by melt spinning and precursor conversion method using the spinnable organic-inorganic hybrid polyborazane modified by the boron nitride nanosheets as raw material, and has the following technical indicators:
[0034] (1) High crystallinity, specifically crystallinity > 90%;
[0035] (2) Excellent mechanical properties, >1.0GPa;
[0036] (3) High density, specifically density ≥ 2.0 g / cm 3 .
[0037] Compared with the prior art, the present invention has the following advantages:
[0038] 1. The spinnable organic-inorganic hybrid polyborazine modified with boron nitride nanosheets described in the present invention, wherein the modified boron nitride nanosheets in the prepared hybrid polyborazane are chemically bonded with the polyborazane to achieve uniform dispersion of the modified boron nitride nanosheets; the prepared hybrid polyborazane can be converted into a high-crystalline boron nitride ceramic material; the prepared hybrid polyborazine precursor has a high ceramic yield and good spinnability.
[0039] 2. The method for preparing a spinnable organic-inorganic hybrid polyborazane modified by boron nitride nanosheets described in the present invention has a simple preparation process, readily available raw materials, and a controllable reaction process. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0041] Figure 1 is an optical photograph of the synthesized hybrid precursor;
[0042] Figure 2 is the FT-IR graph of the hybrid polyborazine precursor;
[0043] Figure 3 is a viscosity-shear rate curve diagram of Examples 1-5 of the present invention and Comparative Example 1;
[0044] Figure 4is a SEM photograph of the fiber spun in Example 4 of the present invention before pyrolysis (A and B are surface and cross-sectional photographs of the fiber before pyrolysis, respectively, and C is an enlarged view of the area marked by a red circle in B, where the presence of modified boron nitride nanosheets can be observed);
[0045] Figure 5 This is an XRD diagram of boron nitride ceramic fiber prepared from the hybrid polyborazine precursor and the polyborazine precursor without BNNS doping in Example 1 of the present invention. DETAILED DESCRIPTION
[0046] The present invention will be further described below in conjunction with the embodiments and drawings.
[0047] The following examples and comparative examples are all carried out according to the steps of the preparation method for synthesizing the modified boron nitride nanosheet-doped organic-inorganic hybrid polyborazine precursor, except that the size and addition ratio of the modified boron nitride nanosheets used are different; the sample addition, transfer and other operations in the experiment are all carried out in an argon glove box, and the argon used is high-purity argon with a purity of ≥99.99%; the protective atmosphere in each example and comparative example is nitrogen, and the nitrogen used has a purity of ≥99.9%; other chemical reagents used, unless otherwise specified, are obtained through conventional commercial channels.
[0048] Embodiment 1:
[0049] A method for preparing a spinnable organic-inorganic hybrid polyborazane modified by boron nitride nanosheets comprises the following steps:
[0050] (1) Preparation of modified boron nitride nanosheets:
[0051] Boron nitride nanosheets and urea were placed in a high-energy ball mill at a mass ratio of 6:1 for 12 hours, and the obtained powder was then washed, filtered, dried, and dispersed in toluene to obtain a modified BNNS (mBNNS) toluene dispersion;
[0052] Depend on Figure 1 It can be seen that the size of mBNNS is 2 μm;
[0053] (2) Preparation of organic-inorganic hybrid polyborazine:
[0054] At room temperature, the mBNNS toluene dispersion was added to the poly[2-propylamino-4,6-bis(methylamino)borazine-tri(methylamino)borazine] (PPMAB) oligomer solution at a mass ratio of 0.1%, and kept at 60°C for 5 hours to allow the modified BNNS to be doped into the borazane oligomer through chemical bonds and methods; the temperature was slowly raised to 180°C, kept for 15 hours, and then cooled to room temperature to obtain the organic-inorganic hybrid polyborazine.
[0055] Depend on Figure 3It can be seen that the apparent viscosity of the organic-inorganic hybrid polyborazane synthesized in this example decreases with increasing shear rate, showing the shear thinning behavior of a pseudoplastic fluid;
[0056] Depend on Figure 5 It can be seen that the crystallinity of the BN ceramic fiber prepared by using the organic-inorganic hybrid polyborazine synthesized by the synthesis method of this embodiment as a raw material is greatly improved.
[0057] Embodiment 2:
[0058] A method for preparing a spinnable organic-inorganic hybrid polyborazane modified by boron nitride nanosheets comprises the following steps:
[0059] (1) Preparation of modified boron nitride nanosheets:
[0060] Boron nitride nanosheets and urea were placed in a high-energy ball mill at a mass ratio of 6:1 for 12 hours, and the obtained powder was then washed, filtered, dried, and dispersed in toluene to obtain a modified BNNS (mBNNS) toluene dispersion;
[0061] Depend on Figure 1 It can be seen that the size of mBNNS is 2 μm;
[0062] (2) Preparation of organic-inorganic hybrid polyborazine:
[0063] At room temperature, the mBNNS toluene dispersion was added to the poly[2-propylamino-4,6-bis(methylamino)borazine-tri(methylamino)borazine] (PPMAB) oligomer solution at a mass ratio of 0.1%, and kept at 160°C for 5 hours to allow the modified BNNS to be doped into the borazane oligomer through chemical bonds and methods; the temperature was slowly raised to 300°C, kept for 15 hours, and then cooled to room temperature to obtain the organic-inorganic hybrid polyborazine.
[0064] Depend on Figure 3 It can be seen that the apparent viscosity of the organic-inorganic hybrid polyborazane synthesized in this example decreases with increasing shear rate, showing the shear thinning behavior of a pseudoplastic fluid;
[0065] Depend on Figure 5 It can be seen that the crystallinity of the BN ceramic fiber prepared by using the organic-inorganic hybrid polyborazine synthesized by the synthesis method of this embodiment as a raw material is greatly improved.
[0066] Embodiment 3:
[0067] A method for preparing a spinnable organic-inorganic hybrid polyborazane modified by boron nitride nanosheets comprises the following steps:
[0068] (1) Preparation of modified boron nitride nanosheets:
[0069] Boron nitride nanosheets and urea were placed in a high-energy ball mill at a mass ratio of 6:1 for 12 hours, and the obtained powder was then washed, filtered, dried, and dispersed in toluene to obtain a modified BNNS (mBNNS) toluene dispersion;
[0070] Depend on Figure 1 It can be seen that the size of mBNNS is 2 μm;
[0071] (2) Preparation of organic-inorganic hybrid polyborazine:
[0072] At room temperature, the mBNNS toluene dispersion was added to the poly[2-propylamino-4,6-bis(methylamino)borazine-tri(methylamino)borazine] (PPMAB) oligomer solution at a mass ratio of 0.5%, and kept at 160°C for 5 hours to allow the modified BNNS to be doped into the borazane oligomer through chemical bonds and methods; the temperature was slowly raised to 180°C, kept for 15 hours, and then cooled to room temperature to obtain the organic-inorganic hybrid polyborazine.
[0073] Depend on Figure 3 It can be seen that the apparent viscosity of the organic-inorganic hybrid polyborazane synthesized in this example decreases with increasing shear rate, showing the shear thinning behavior of a pseudoplastic fluid;
[0074] Depend on Figure 5 It can be seen that the crystallinity of the BN ceramic fiber prepared by using the organic-inorganic hybrid polyborazine synthesized by the synthesis method of this embodiment as a raw material is greatly improved.
[0075] Embodiment 4:
[0076] A method for preparing a spinnable organic-inorganic hybrid polyborazane modified by boron nitride nanosheets comprises the following steps:
[0077] (1) Preparation of modified boron nitride nanosheets:
[0078] The boron nitride nanosheets and urea were placed in a high-energy ball mill at a mass ratio of 6:1 and ball-milled for 36 hours. The obtained powder was then washed, filtered, dried, and dispersed in toluene to obtain a modified BNNS (nBNNS) toluene dispersion.
[0079] Depend on Figure 1 It can be seen that the size of nBNNS is 400nm;
[0080] (2) Preparation of organic-inorganic hybrid polyborazine:
[0081] At room temperature, the nBNNS toluene dispersion was added to the poly[2-propylamino-4,6-bis(methylamino)borazine-tri(methylamino)borazine] (PPMAB) oligomer solution at a mass ratio of 0.1%, and kept at 60°C for 5 hours to allow the modified BNNS to be doped into the borazane oligomer through chemical bonds and methods; the temperature was slowly raised to 180°C, kept for 15 hours, and then cooled to room temperature to obtain the organic-inorganic hybrid polyborazine.
[0082] Depend on Figure 3 It can be seen that the apparent viscosity of the organic-inorganic hybrid polyborazane synthesized in this example decreases with increasing shear rate, showing the shear thinning behavior of a pseudoplastic fluid;
[0083] Depend on Figure 5 It can be seen that the crystallinity of the BN ceramic fiber prepared by using the organic-inorganic hybrid polyborazine synthesized by the synthesis method of this embodiment as a raw material is greatly improved.
[0084] This embodiment also provides a BN fibril (BN ceramic material) such as Figure 4 As shown, the modified BNNS was successfully incorporated into the BN fibrils, and was obtained by melt spinning using the organic-inorganic hybrid polyborazine synthesized by the synthesis method of this embodiment as a raw material.
[0085] Embodiment 5:
[0086] A method for preparing a spinnable organic-inorganic hybrid polyborazane modified by boron nitride nanosheets comprises the following steps:
[0087] (1) Preparation of modified boron nitride nanosheets:
[0088] The boron nitride nanosheets were directly dispersed in toluene without ball milling to obtain a modified BNNS (BNNS) toluene dispersion;
[0089] Depend on Figure 1 It can be seen that the size of BNNS is 10 μm;
[0090] (2) Preparation of organic-inorganic hybrid polyborazine:
[0091] At room temperature, the BNNS toluene dispersion was added to the poly[2-propylamino-4,6-bis(methylamino)borazine-tri(methylamino)borazine] (PPMAB) oligomer solution at a mass ratio of 0.1%, and kept at 60°C for 5 hours to allow the modified BNNS to be doped into the borazane oligomer through chemical bonds and methods; the temperature was slowly raised to 180°C, kept for 15 hours, and then cooled to room temperature to obtain the organic-inorganic hybrid polyborazine.
[0092] Depend on Figure 3 It can be seen that the apparent viscosity of the organic-inorganic hybrid polyborazane synthesized in this example decreases with increasing shear rate, showing the shear thinning behavior of a pseudoplastic fluid;
[0093] Depend on Figure 5 It can be seen that the crystallinity of the BN ceramic fiber prepared by using the organic-inorganic hybrid polyborazine synthesized by the synthesis method of this embodiment as a raw material is greatly improved.
[0094] Embodiment 6:
[0095] A method for preparing a spinnable organic-inorganic hybrid polyborazane modified by boron nitride nanosheets comprises the following steps:
[0096] (1) Preparation of modified boron nitride nanosheets:
[0097] Boron nitride nanosheets and 15 N-labeled urea was placed in a high-energy ball mill at a mass ratio of 6:1 for 12 h, and the resulting powder was washed, filtered, dried, and dispersed in toluene to obtain modified BNNS ( 15 NH2-mBNNS) toluene dispersion;
[0098] (2) Preparation of organic-inorganic hybrid polyborazine:
[0099] At room temperature, 15 NH2-mBNNS toluene dispersion was added to the poly[2-propylamino-4,6-bis(methylamino)borazine-tri(methylamino)borazine](PPMAB) oligomer solution at a mass ratio of 0.1%, and kept at 60°C for 5 hours to allow the modified BNNS to be doped into the borazane oligomer through chemical bonds and methods; the temperature was slowly raised to 180°C, kept for 15 hours, and then cooled to room temperature to obtain organic-inorganic hybrid polyborazine.
[0100] Comparative Example:
[0101] The difference from Example 1-6 is that no modified boron nitride nanosheets are added in step (2).
[0102] Depend on Figure 5 It can be seen that the boron nitride ceramic material obtained by transforming the precursor prepared under these conditions has a low degree of crystallinity.
[0103] The organic-inorganic hybrid polyborazane synthesized in Examples 1-5 and Comparative Example 1 was characterized by FT-IR to compare its molecular structure. The results are as follows: Figure 2 shown.
[0104] It can be seen that the molecular structure of the precursor obtained in the example is not much different from that in the comparative example, which indicates that the types of chemical bonds in the molecular structure of the hybrid polyborazine precursor after modified BNNS doping have not changed, and only the comparative example has changed.
[0105] Although the present invention has been illustrated and described with specific embodiments, it will be appreciated that many other changes and modifications may be made without departing from the spirit and scope of the present invention. It is therefore intended that all such changes and modifications that fall within the scope of the present invention be included in the appended claims.
Claims
1. A method for preparing a spinnable organic-inorganic hybrid polyborazane modified with boron nitride nanosheets, characterized in that: The following steps are involved: (1) Preparation of modified boron nitride nanosheets: The boron nitride nanosheets and the modifier were mixed in a mass ratio of 6:1, and then ball-milled in a high-energy ball mill. The resulting powder was then washed, filtered, dried, and dispersed in a solvent in a mass volume ratio of 2 g:10 mL to obtain a modified BNNS dispersion. The modified BNNS dispersion, wherein the BNNS size is 100nm-10μm and the thickness is 10nm-20nm; The modifier is an amino group-containing compound selected from NH2R1, NHR1R2 amine compounds, or a mixture of one or more of other amino-containing compounds, in any proportion, wherein R1 and R2 are CH3, CH2CH3, CH2CH2CH3 or other alkyl groups; The solvent is selected from toluene, xylene and chlorobenzene; (2) Preparation of organic-inorganic hybrid polyborazine: At room temperature, the modified BNNS dispersion obtained in the previous step is added to the borazane oligomer solution at a mass ratio of 0.1%-0.5%, and the concentration of the borazane oligomer solution is 10mg / mL-100mg / mL. The solution is kept warm at low temperature to allow the modified BNNS to be doped into the borazane oligomer through chemical bonds and methods; the temperature is slowly raised to a high temperature and kept warm, and after cooling to room temperature, an organic-inorganic hybrid polyborazine is obtained; The borazane is selected from one or a mixture of borane, cycloborazine, trichlorocycloborazine, alkylaminoborane or ammonia borane, and the mixture is in any proportion; The oligomer is selected from one of a dimer, a trimer and a tetramer; The heat preservation at low temperature is a temperature of 60°C-160°C and a time of 1h-5h; The slow heating to high temperature insulation is heating to 180°C-300°C, and the insulation time is 1h-15h.
2. The method for preparing a spinnable organic-inorganic hybrid polyborazane modified by boron nitride nanosheets according to claim 1, characterized in that: The ball milling process in step (1) is performed for 12 h to 48 h at a rotation speed of 400 r / min to 1000 r / min.
3. The method for preparing a spinnable organic-inorganic hybrid polyborazane modified by boron nitride nanosheets according to claim 1, characterized in that: The modified BNNS dispersion described in step (1), wherein the BNNS has a size of 400 nm-2 μm and a thickness of 10 nm-20 nm.
4. A spinnable organic-inorganic hybrid polyborazane modified with boron nitride nanosheets, characterized in that: The method for preparing a spinnable organic-inorganic hybrid polyborazine modified by boron nitride nanosheets according to any one of claims 1 to 3 is used to obtain the spinnable organic-inorganic hybrid polyborazine modified by boron nitride nanosheets, which has the following technical indicators: the modified boron nitride nanosheets are combined with the polyborazine by chemical bonding, the ceramic yield is ≥65%, and the spinnability E η =1.0 kJ / mol.
5. A BN ceramic material, characterized in that: The spinnable organic-inorganic hybrid polyborazane modified by boron nitride nanosheets as claimed in claim 4 is prepared by melt spinning and precursor conversion method, and has the following technical indicators: crystallinity>90%, mechanical properties>1.0GPa, density≥2.0g / cm 3 .
Citation Information
Patent Citations
Hydroxylated modified boron nitride nano material, preparation method and application thereof
CN109939719A
Boron-containing ceramic precursor as well as preparation method and application thereof
CN115216018A
Multi-functional BN-BN composite
EP2831017A2
Hexagonal boron nitride nanosheet / ceramic nanocomposite powder and producing method of the same, and hexagonal boron nitride nanosheet / ceramic nanocomposite materials and producing method of the same
US20150069288A1